The effect of entrepreneurial self-efficacy and entrepreneurial self-identity on entrepreneurial goal intentions of female and male college students in Zimbabwe - Takawira Munyaradzi Ndofirepi (Administrative Sciences, 2022)
This article investigated how entrepreneurial self-identity and self-efficacy interact to affect the entrepreneurial goal intentions of a sample of female and male college students in Zimbabwe. Researchers are urged to examine these factors' combined influence, given that earlier studies looked at their effects separately. To achieve the research goal, a cross-sectional survey using a self-completion questionnaire on a convenience sample of 262 respondents was conducted in Zimbabwe among college students. The results confirmed that entrepreneurial self-identity and self-efficacy had statistically significant direct effects on the intention to pursue an entrepreneurial goal. They also confirmed that the relationship between entrepreneurial self-efficacy and entrepreneurial goal intention was mediated by entrepreneurial self-identity. The study, however, found no statistically significant differences in the pattern of results between males and females. The study adds to the body of knowledge by proposing and testing a conceptual model that has never been considered before. The findings of the study have implications for the formulation of interventions and policies aimed at promoting entrepreneurship.
Keywords: 350; intentions; mediation; moderation; self-efficacy; self-identity